Flexible Job Shop Scheduling Problem-Solving Using Apiary Organizational-Based Optimization Algorithm - Al-Sharqi, Mais A.; Sadiq, Ahmed T.; Al-mamory, Safaa O. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Flexible job shop scheduling problem (FJSSP) is a complex and challenging problem that plays a crucial role in industrial and manufacturing production. FJSSP is an expansion of the standard job shop scheduling problem (JSSP). One of FJSSP’s objectives that the manufacturing system competing for is minimizing the makespan. This paper uses a new nature-inspired metaheuristic optimization algorithm called the Apiary Organizational-Based Optimization algorithm (AOOA) to solve the FJSSP. This Algorithm simulates the organizational behavior of honeybees inside the apiary and translates their activities and vital processes during their lifecycle into phases that can solve such NP-hard problems. Two benchmark datasets, Brandimarte and Hurink, with 10 MK instances and 24 (edata, rdata, and vdata) instances respectively, were used to demonstrate the ability of AOOA to solve FJSSP. Moreover, the results of AOOA were compared with a set of state-of-the-art algorithms and statistically measured using the paired samples t-test and p-value, RPD, and group-based superiority statistical analysis to test its performance. AOOA outperformed Elitism GA, Enhanced GA, Improved GA, and MOGWO in solving all 10 MK instances and HICSA in solving 9 MK instances out of 10. Moreover, AOOA overcame CS, CS-BNG, CS-ILF, CHA, and MCA in solving 24, 12, 12, 23, and 24 instances of edata, rdata, and vdata, respectively. AOOA proved its robustness, showing promising outcomes.